Leather House Creative / Bakhtiar Abd Rani ... [et al.] - Abd Rani, Bakhtiar; Abd Latif, Muttaqin; Ahmad, Azhar; Mohammad Yusoff, Mohammad Shabrizan (2002)
Leather House Creative is a company that used leather to provide a business for public either man and woman. We will be operating on 1 st January 2003. As a new company we believe that our business will face with many competitors. Therefore, we have made a research or studies about this business. The business location that we choose is at Central Square the popular shopping complex at Sungai Petani. We choose this location because this place is the main attraction at Sungai Petani. We think that we can make more profit in this popular place. To open this business we need capital about RM60,000 .Where it was contribute from every partner about RM60,000 we do not borrow money from bank because our business is new and we want to start from below. Although there are many product made by leather in Malaysia, there are just a few company that a Bumiputra. But we believe that the person likes to try something new. Nowadays many people are now looking to item made by leather examples like wallet, shoes, jackets and many more. Our product also is a comfortable price and more cheap that other competitors. As a conclusion we hope that our company, Leather House Creative can compete with order that have establish in this leather industry.